The impact of COVID-19 on dengue cases in low- and middle-income countries: a systematic review - Rahastri, Ajeng; Sulistyawati, Sulistyawati (Intelektual Pustaka Media Utama, 2024)
The WHO declared the COVID-19 pandemic on March 11, 2020, impacting infectious disease surveillance in low-resource, low-income countries, low- and middle-income countries (LMICs). Governments are focusing on COVID-19 reduction, including healthcare workers and epidemiological teams. A comprehensive literature review was conducted to assess this impact. After examining over 19,000 studies, only six were found to provide relevant data. Our analysis revealed that the pandemic substantially affected dengue incidence. The total number of articles obtained was 19,382. Out of the 136 articles screened based on their abstracts, only six were selected for data extraction. The databases utilized in this article were Pubmed and NCBI. Based on the chosen papers, we discovered that the COVID-19 pandemic has had a notable impact on the occurrence of dengue compared to the period before the pandemic emerged. The occurrence of dengue varied in several nations, such as Peru, Brazil, Sri Lanka, India, and Malaysia. This variation can be attributed to factors such as reliance on traditional approaches, for example community health volunteers in epidemiological investigations. Additionally, misdiagnoses by healthcare professionals due to the similarity of symptoms with COVID-19 have been reported during the pandemic. While the prevalence of dengue fever cases has generally declined in low- and middle-income countries (LMICs), one country has experienced an increased case. This trend is possibly linked to heightened pandemic surveillance and changes in mosquito populations. To improve monitoring and surveillance, a digital approach is proposed.